Para desenvolver a Terra: memórias e notícias de Geociências no espaço lusófono - M. H. Henriques (Documentos, 2012)
This work gathers a series of contributions presented at the 1st International Conference of Geosciences in the CPLP on 14th to 16th May 2012 in the Auditorium of the Rector's Office of the University of Coimbra. It presents studies by various teams affiliated to different institutions from the Community of Portuguese-speaking Countries (CPLP), including technical approaches and innovative research, and the application of scientific knowledge to solving the most pressing problems of our times. These high-interest works document problems and solutions from around the Portuguese-speaking world, revealing the great importance of the concepts, geotechnologies, prospection, geology, engineering and mineral resources for the development, wellbeing and progress of humanity.